BACTERIOLOGICAL EXAMINATION OF PUS SAMPLE COLLECTED FROM A COW: A CASE STUDY - Ganguly, Subha (International Journal of Research -GRANTHAALAYAH, 2016)
The present article reports on the bacteriological examination and antibiotic sensitivity test of pus sample collected from an abscess at the neck region of a cow.